PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIPE TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Siska Puspita Sari; Sukanto Sukandar Madio (Institut Pendidikan Indonesia, 2013)
Abstract This study aims to determine whether the learning outcomes of learning mathematics that uses models of type kooperatipe think pair share ( TPS ) is better than that using learning model konvensional.Dari normality test results of initial test data shows that the initial test scores in the experimental class were normally distributed , whereas scores initial tests on the control class distribution is not normal , so proceed with testing at the Mann Whitney test with significance level 0.05.karena the initial tests at the conclusion can not start capability differences between the experimental class and the control class followed by ternormalisasi.berdasarkan gain test data analysis results can indicate that the initial capacity of the two groups can be concluded there is influence . while the results obtained from the final test at the significant tarap 00:05 . because t > t table then Ho ditolak.dengan It can be concluded that there are significant mathematical achievement of students who use cooperative learning model think pair share .